Pengaruh Kinerja Keuangan dan Sustainability Report terhadap Harga Saham (Studi Kasus Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2022-2023) - Imannisa, Maulida; Yudi, Yudi; Gowon, Muhammad (Jurusan Akuntansi FEB Universitas Jambi, 2025)
This study is entitled “The Effect of Financial Performance and Sustainability Report on Stock Prices (Case Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2022-2023 Period)”. The purpose of this study is to determine the effect of Return on Assets, Return on Equity, Debt to Equity Ratio, Earning per Share, and Sustainability Report on stock prices of Property and Real Estate companies listed on the Indonesia Stock Exchange for the 2022-2023 period. The data used in this study are secondary data and use multiple linear regression analysis. Based on the results of the descriptive analysis, it is known that the Return on Assets (X1) variable, Return on Equity (X2) variable, Debt to Equity Ratio (X3) variable, Sustainability Report (X5) variable has an insignificant effect on stock prices. While the Earning per Share (X4) variable has a significant effect on stock prices.